Prevention and management of adverse events of novel agents in multiple myeloma: a consensus of the European Myeloma Network - Ludwig, Heinz; Goldschmidt, Hartmut (Leukemia, 2018)
During the last few years, several new drugs have been introduced for treatment of patients with multiple myeloma, which have significantly improved the treatment outcome. All of these novel substances differ at least in part in their mode of action from similar drugs of the same drug class, or are representatives of new drug classes, and as such present with very specific side effect profiles. In this review, we summarize these adverse events, provide information on their prevention, and give practical guidance for monitoring of patients and for management of adverse events.